2017
DOI: 10.1038/s41535-017-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Rewritable ferroelectric vortex pairs in BiFeO3

Abstract: Ferroelectric vortex in multiferroic materials has been considered as a promising alternative to current memory cells for the merit of high storage density. However, the formation of regular natural ferroelectric vortex is difficult, restricting the achievement of vortex memory device. Here, we demonstrated the creation of ferroelectric vortex-antivortex pairs in BiFeO 3 thin films by using local electric field. The evolution of the polar vortex structure is studied by piezoresponse force microscopy at nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Experimental design to create and separate a topological pair Electric fields induced by a tip create stray fields around the tip along concentric inward directions when a negative bias is applied to the tip. [16][17][18][19][20][21][22] Figure 2a shows a schematic of local polarization switching. Applying a negative bias to a point in a uniformly polarized medium induces a ferroelectric vortex underneath the tip.…”
Section: Sample Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental design to create and separate a topological pair Electric fields induced by a tip create stray fields around the tip along concentric inward directions when a negative bias is applied to the tip. [16][17][18][19][20][21][22] Figure 2a shows a schematic of local polarization switching. Applying a negative bias to a point in a uniformly polarized medium induces a ferroelectric vortex underneath the tip.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…15 Recently, Li et al demonstrated the creation of ferroelectric vortex-antivortex pairs using a local electric field. 16 They successfully observed the electric formation of topological networks consisting of two or three vortex-antivortex pairs and temporal evolution of their configurations. Despite the achievement, it remains a tantalizing challenge to create, observe, and manipulate a single vortex-antivortex pair from the aspect of a low-lying elementary excitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these additives are well understood and controlled, the FEDW conduction as a novel functionality would be offered an additional degree of freedom. In fact, recent studies did reveal some unique exotic domains such as bubble, flux‐closure vortex, and center‐type topological states in nanoscale ferroelectrics, which also add more ingredients into the enthralling DW functionalities. In view of the tantalizing properties in both domain wall conductance and nanoferroelectrics, it is highly promising and extremely important to look into the FEDW conduction behaviors in size‐confined nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…2Ha-TaSe 2 also undergoes an ICCDW phase transition at T ICDW ≈ 122 K, then locksin to a commensurate-charge-density waves (CCDW) state at T CCDW ≈ 90 K [14,15], and finally to a superconducting state at T c ≈ 0.14 K [16,17]. T c will increase with S or Te doping [18,19], or Ni or Pd intercalations [20,21], or under pressure [9]. 3R-TaSe 2 is not stable [22], but with Te, Mo or W doping, it becomes stable and superconducting at T C of about 2 K [23].…”
Section: Introductionmentioning
confidence: 99%